Assessment and comparison of the solar radiation distribution inside the main commercial photovoltaic greenhouse types in Europe. (October 2018) - Cossu, Marco; Cossu, Andrea; Deligios, Paola A.; Ledda, Luigi; Li, Zhi; Fatnassi, Hicham; Poncet, Christine; Yano, Akira
Abstract: The application of the photovoltaic (PV) energy to the European greenhouse industry has led to installations designed to maximise the energy production but detrimental for the greenhouse crops, due to the effect of shading of the PV panels on the roof. To assess these issues, the first step is to characterize the PV greenhouse microclimate, especially in terms of solar radiation at canopy level. After a comprehensive review of the current state-of-art of the PV greenhouse sector, four representative commercial PV greenhouse types are compared, with a percentage of the area covered with PV panels (PV cover ratio) ranging from 25% to 100%. The aim is to define the general relations between the main design parameters (PV cover ratio, greenhouse height and orientation, checkerboard pattern) and the available solar radiation, to provide original information on the design of next-generation PV greenhouses with improved agronomic sustainability. The yearly global radiation decreased averagely by 0.8% for each additional 1.0% PV cover ratio and increased by 3.8% for each further meter of gutter height. The N-S orientation increased the average cumulated global radiation on the greenhouse area by 24%, compared to the E-W orientation. Both the checkerboard pattern and the N-S orientation improved the uniformity of light distribution. All PV greenhouse types are provided with light distribution maps to evaluate the light variability on the greenhouse area. The light distribution is crucial to support adequate agronomic plans for both preexisting and new PV greenhouses, aiming to sustainable mixed systems for both energy and crop production. Highlights: The solar light distribution was calculated on the main PV greenhouse types. The effect of design criteria on the sustainability of PV greenhouses is estimated. The available global radiation decreases by 0.8% for each additional 1.0% PV area. Each additional meter of gutter height increases the global radiation of 3.8%. The N-S orientation allows averagely 24% more global radiation than E-W orientation.